Break Even Point sebagai Alat Perencanaan Laba pada PT Perkebunan Nusantara VIII Kebun Rancabali Bandung - Jawa Barat - Dyah Puspasari; Tri Handayani (Jurnal Ilmiah ESAI, 2016)
Rancabali Tea Garden located in District Rancabali Bandung Regency West Java Province is one company that processes black tea. This company is a family business that has started operating optimally since 1870. In order to keep exist in tea agribusiness and can make policy about production, price, and cost, hence an analysis about Break Even Point (BEP) to the company is needed. The objective of this research is to calculate the production and revenue of Rancabali Tea Garden in order to achieve Break Even Point, to analyze the economic profitability of Rancabli Tea Garden, and to examine the benefits of Rancabali Tea Garden if there is a change of product selling price, production cost, and production amount. The method used in this research is descriptive method, with an implementation of technique in the form of case study. The research location and the sample were selected purposively (PT. Perkebunan Nusantara VIII Rancabali Tea Garden of Rancabali District Bandung Regency West Java Province). It is found that the production and reception of Rancabali Tea Garden in the event of Break Even Point is 519 Kg and Rp.9,684,142 for 2013, 502 Kg and Rp.10,343,280 for the year 2014, and 521 Kg and Rp.11,145,772 for 2015. Economic Profitability of Rancabali Tea Garden in 2013 is 68%, by 2014 by 73% and by 2015 by 81%. This shows that Rancabali Tea Garden is already effective in using its wealth to generate profits. Keywords: Break Event Point, Profit Planning, Tools